Design and Implementation of a High-Reliability Underwater Wireless Optical Communication System Based on FPGA - Tengfei Han; Peng Ding; Nan Liu; Zhengguang Wang; Zhenyao Li; Zhanqiang Ru; Helun Song; Zhizhen Yin (Applied Sciences)
In order to meet the reliability requirements of communication for underwater resource exploration, this study develops an underwater wireless optical communication (UWOC) system utilizing a blue semiconductor laser as the light source. At the receiver, a fully digital automatic gain control (AGC) module, implemented on a field-programmable gate array (FPGA), is designed to mitigate signal fluctuations induced by underwater turbulence. Digital filtering techniques, including median filtering (MF) and bilateral edge detection filtering (BEDF), are also employed to improve signal demodulation reliability. An improved Reed–Solomon (RS) coding scheme is further adopted to significantly reduce the bit error rate (BER). The design of a highly reliable UWOC system was realized based on the above techniques. The system’s performance was evaluated across a range of signal-to-noise ratios (SNRs) and bubble intensities. The results show that the digital AGC module can provide a gain range from −3.2 dB to 16 dB, adapting to varying signal strengths, which greatly bolsters the system’s resilience against underwater turbulence. Filtering techniques and RS coding further enhance the system’s immunity to interference and reduce the system BER. Communication experiments were conducted over various distances under three distinct water quality conditions. The results demonstrate that, within the detection range of the avalanche photodiode (APD), the system consistently maintained a BER below 3.8 × 10−3 across all water types, thereby confirming its high reliability. In clear seawater, the system demonstrated reliable information transmission over a 10 m distance at a data rate of 10 Mbps, achieving a BER of 2 × 10−8. Theoretical calculations indicate that the maximum transmission distance in clear seawater can reach 111.35 m.